Answer:
http://eldata2.neu.topica.vn/TXTOKT02/Giao%20trinh/03_NEU_TXTOKT02_Bai2_v1.0014109205.pdf
Step-by-step explanation:
I dont know im trying to figure that out
Answer:
y =
x - 2
Step-by-step explanation:
<u>The answer to this problem is a simple plug-in of the given values into the slope-intercept formula.</u>
Slope intercept formula: y = mx + b
(m = slope)
(b = y intercept)
If the equation has a slope of m =
, then the slope-intercept form would be:
y =
x
If the y-intercept of an equation is (0 , -2), then the slope intercept form would be:
y = mx - 2
<u>Putting both of these values into an equation would give option A:</u>
y =
x - 2
3y - y + 8 - 2 = 20
3y - y = 2y
8 - 2 = 6
2y + 6 = 20
2y = 20 - 6
y = 10 - 3
the answer is: y = 7
1. x = -4 ; f(x) = -(-4) = 4
2. x = -3 ; f(x) = 2(-3) + 1 = -5
3. x = 0 ; f(x) = 2(0) + 1 = 1
4. x = 2 ; f(x) = 2 + 3 = 5
5. x = 5 ; f(x) = 5 + 3 = 8